1995
DOI: 10.1007/bf03168407
|View full text |Cite
|
Sign up to set email alerts
|

The “Fisherman’s Waders” sign in a bone scan of inferior vena cava thrombosis associated with nephrotic syndrome

Abstract: This paper presents a 61-year-old male patient with nephrotic syndrome, hypercoagulability and IVC thrombosis. Increased soft tissue uptake below the level of the mid chest was seen in his bone scan. The term "Fisherman's Waders" sign is suggested for this finding, whose recognition may permit the identification of inferior vena cava obstruction in bone scans. The existence of a cavo-portal shunt was also confirmed by dynamic scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…20,46 Inflammatory bowel disease, nephrotic syndrome and sepsis predispose to venous thromboses owing to associated risks of severe dehydration, protein/anticoagulant loss and elevated inflammatory response. [47][48][49][50] A further variant of primary IVC thrombosis, occasionally termed obliterative or membranous hepatocavopathy, most commonly occurs in the hepatic portion (as the name suggests), and is characterised by a thrombus organising into a fibrous, membranous obstruction of the IVC. The cause of such primary IVC thrombosis is often idiopathic.…”
Section: Acquired Ivc Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…20,46 Inflammatory bowel disease, nephrotic syndrome and sepsis predispose to venous thromboses owing to associated risks of severe dehydration, protein/anticoagulant loss and elevated inflammatory response. [47][48][49][50] A further variant of primary IVC thrombosis, occasionally termed obliterative or membranous hepatocavopathy, most commonly occurs in the hepatic portion (as the name suggests), and is characterised by a thrombus organising into a fibrous, membranous obstruction of the IVC. The cause of such primary IVC thrombosis is often idiopathic.…”
Section: Acquired Ivc Thrombosismentioning
confidence: 99%
“…20,46 Inflammatory bowel disease, nephrotic syndrome and sepsis predispose to venous thromboses owing to associated risks of severe dehydration, protein/anticoagulant loss and elevated inflammatory response. 47 50…”
Section: Aetiologymentioning
confidence: 99%
“…[7] Another study reported Fisherman's Waders' sign in a lymphoma patient complicated by IVC obstruction seen on CT and bone scans and in nonthrombotic portal hypertension. [8] This represents a rare report of Wader's sign from IVC syndrome in metastatic prostate cancer highlighting its characteristic imaging appearance that should prompt confirmatory anatomic imaging.…”
mentioning
confidence: 78%
“…4 Previously reported causes of localization of bone radiotracer in vascular lesions include femoral artery calcification, 7,8 aortic aneurysms, 9 phlebitis, 10 and venous thrombosis. [11][12][13][14] However, despite the high prevalence of phleboliths, uptake of bone radiotracer has been very rarely reported in the literature. 15 …”
Section: Figurementioning
confidence: 93%